Tabligh dalam Sistem Dakwah - AS, Enjang (Prophetica, 2009)
Tabligh is one of the most popular approaches in dakwah activites and it can be called dawah bi ahsan al-qawl (dakwah by manner speech approach). Tabligh methods can be divided to; khithabah which at least can be categorized to khithabah diniyah (religious speech) and khithabah tatsiriyah (incidential speech); kitabah which categorized to printed and electronic media; and ilam which categorized to radio and television broadcast. These three methods of tabligh are the most important approaches in a huge system of dakwah.(Tabligh adalah salahsatu pendekatan paling populer dalam kegiatan dakwah. Tabligh juga dapat disebut dawah bi ahsan al-qawl (dakwah dengan pendekatan pidato). Metode tabligh terbagi menjadi : Khitabah yang terdiri dari kategori Khitabah Diniyah (ceramah keagamaan) dan Khitabah Tatshiriyah (ceramah waktu tertentu); Kitabah yang dibagi menjadi media cetak dan elektronik/ dan ilam yang terdiri dari penyiaran radio dan televisi. tiga metode tabligh ini adalah pendekatan paling penting dalam sistem besar dakwah). KeywordsTabligh, Khitabah, Kitabah, !lam dan Dakwah Islam